The Role of Salesmen in Gaining customer Loyalty: a field study in the Family Mall in Salmaniya) Halabja Technical Institute / Salmaniya Technical University / Kurdistan Region. - حبيب الله, شاخەوان جمال; جميل, مەريوان مهدي (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The research aims to work on showing the role of salesmen in gaining customer loyalty and the extent of the contribution of the role of salesmen in gaining customer loyalty in the Family Mall in Sulaymaniyah Governorate. And that the research problem is to know the relationship and the effect between salesmen and gain customer loyalty? What is the nature of the relationship and the effect between salesmen and customer loyalty? The researchers used the statistical methods in the SPSS statistical package for social sciences. using statistical treatments such as percentages, arithmetic averages, standard deviation, Cronbach’s alpha coefficient, Pearson correlation coefficient and effect coefficient. Therefore, the descriptive analytical approach was followed, and the sample was chosen randomly. 110 questionnaires were distributed to a sample of customers in the family mall in Sulaymaniyah Governorate, and 106 of them were returned. Among the most important results of the study is that there is a significant relationship with statistical significance between the role of salesmen and gaining customer loyalty, and there is a correlation between the dimensions of the independent variable and the dependent variable, as the dimension of salesmen’s ability has a more role than other dimensions in gaining customer loyalty, and in light of this result The study’s recommendation was to retain the ability of salesmen in the Family Mall and develop their skills in terms of tact and convince customers to buy goods and services.